DOCUMENT CONVERTER USING SMARTPHONE TO REFRESHABLE BRAILLE READER - Sukri, Ahmad Nasif (Universiti Teknologi PETRONAS, 2016)
Among the problems faced by vision-impaired people is to get wide access of written knowledge and information [1]. They depend solely on Braille language and recorded speech to access information. Due to recent growth of technology in embedded world, the development of braille display emerges rapidly. However, blind people use this technology seldom because it is costly. Plus, the development and progress on this technology start to decrease due to high development cost [2]. Thus, this project proposes a novel idea to design a system-integrated solution for handheld document converter with the braille and redesigning the mechanism of braille dot movement.